The Signal Warning Detector (SWAD) for Sustainable Working Environment at Highways - Jumari, Mohamad Zhairul Iqumal; Hassan, Suhaimi; Mat Nadir, Mohamad Amirul; Mohd Yusof, Norbazlan; Ikhsan, Mohamad Shah; Mohd Nor Azman, Muhammad Azimuddin; Mohd Sarif, Muhammad Azim Farhi; Abdul Rashid, Muhammad Amir Raauf; Nik Aziz, Nik Nazmi Amir; Yusof, Mohd Sallehuddin; Ismon, Maznan; Zakaria, Hanis; et al. (International Journal of Integrated Engineering, 2022)
Work environment in highway construction are hazardous due to the particular dynamic and limited workspace availability. Within highway work zones, a variety of encounters involving employees, passing cars, and moving construction equipment exists, creating risky situations that may result in injury or death. Active approaches, such as the deployment of intrusion detection and alert devices in highway employees and the construction and maintenance of transportation infrastructure, can be effective in reducing these unforeseen situations. The study focus on development of the emergency signal system for the safety of highway workers was carried out to prevent accidents or danger from happening in the straight emergency line on the highway by developing a system of hazard detectors using a distance sensor. Therefore, the development of the Signal Warning Detector (SWAD) for the safety of highway workers was carried out to prevent accidents or danger from happening in the straight emergency line on the highway by developing a system of hazard detectors using a distance sensor. The distance sensor sensed the target at a certain distance and transmitted the signal emitted through the siren device and the emergency lamp mounted on the PLUS Malaysia Berhad (PLUS) car, while the signal was also transmitted to the receiver to create a danger signal to alert the worker by vibrating the vibrator motor located at the worker’s hand. The study findings show that commercially accessible technologies have the ability to improve employee health in the work zone by providing early signal warning as vibration. This study adds to the knowledge base by offering methods for the collection and application of intruder sensing technologies for active protection in the work zone. The data produced in the result reveals that by performing the study, it was possible to find the best parameter setting for the Danger Signal Detector system. The farthest distance observed was at 14° of angle, 2.2 meter distance from center, and 1.8 meter sensor height.